THE CC GUY : ENHANCING COMPREHENSION OF CONTINUITY CORRECTION - Syah Runniza, Ahmad Bakri; Noriham, Bujang; Aidil Azli, Alias (2023)
In statistics, continuity correction is a crucial modification applied when approximating a discrete distribution (a Binomial or Poisson distribution) by a continuous distribution (a normal distribution). To adjust the discrete value(s), students commonly add or subtract 0.5 as the first step in solving problems related to this topic. However, a preliminary study found that many students need help with the adjustment. The CC Guy was created as a creative solution to this problem to increase students' understanding of continuity correction and facilitate precise adjustments. The CC Guy easily presents the concept of continuity correction by incorporating visualization techniques, allowing students to grasp and apply it more effectively in solving questions. A preliminary survey involving 72 students was conducted to evaluate the effectiveness of The CC Guy. Impressively, 93.1% of the participants agreed that The CC Guy improved their ability to solve questions related to continuity correction. Additionally, an overwhelming majority of 98.6% expressed a strong willingness to recommend this approach to their fellow friends studying these topics. This method empowers students to negotiatethe difficulties of continuity correction with greater ease and confidence, especially for visual learners, by providing a user-friendly and visually appealing platform. In conclusion, The CC Guy is an effective attempt to close the continuity correction comprehension gap. It makes a significant contribution to the field of statistical education. It can potentially improve learning outcomes in this area by enabling students to overcome the uncertainties and challenges related to this fundamental statistical concept.